Antagonist of the neurokinin-1 receptor curbs neuroinflammation in ex vivo and in vitro models of Lyme neuroborreliosis. Issue 1 (December 2015) - Martinez, Alejandra; Ramesh, Geeta; Jacobs, Mary; Philipp, Mario
Abstract Background Lyme neuroborreliosis (LNB) can affect both the peripheral (PNS) and the central nervous systems (CNS); it is caused by the spirocheteBorrelia burgdorferi . The neuropeptide substance P (SP) is an important mediator of both neuroinflammation and blood-brain barrier dysfunction, through its NK1 receptor. Increased levels of SP have been shown to correlate with cell death. The present study used both ex vivo and in vitro models of experimentation to determine if the inflammatory mediator production and concomitant cell death caused by exposure of neural tissues and cells toB. burgdorferi could be attenuated by treatment with a NK1 receptor antagonist. Methods We incubated normal rhesus frontal cortex tissue explants (CNS) and primary cultures of rhesus dorsal root ganglia cells (PNS) with liveB. burgdorferi and tested the effectiveness of the NK1 receptor antagonist L703, 606 in attenuating inflammatory immune responses and neuronal and glial damage. Culture supernatants and tissue lysates were subjected to multiplex ELISA to quantify immune mediators, while the cells were evaluated for apoptosis by the in situ TUNEL assay. In addition, we identified immune mediators and producer cells in tissue sections by immunofluorescence staining and confocal microscopy. Results Co-incubation of both CNS tissues and PNS cells with the NK1 receptor antagonist attenuated bacterially induced increases in inflammatory cytokine and chemokine production, particularly, IL-6, CXCL8, and CCL2, and reduced apoptosis levels. Confocal microscopy confirmed that neurons and glial cells are sources of these immune mediators. These results suggest that NK1 R antagonist treatment is able to reduce downstream pro-inflammatory signaling, thereby indicating that its systemic administration may slow disease progression. Conclusions We propose that SP contributes to neurogenic inflammation in LNB, and provide data to suggest that an NK1 receptor antagonist may represent a novel neuroprotective therapy.